ChemInform Abstract: Crystal Structure of Garnet‐Related Li‐Ion Conductor Li7—3xGaxLa3Zr2O12 : Fast Li‐Ion Conduction Caused by a Different Cubic Modification?. Issue 23 (May 2016) - Wagner, Reinhard; Redhammer, Guenther J.; Rettenwander, Daniel; Senyshyn, Anatoliy; Schmidt, Walter; Wilkening, Martin; Amthauer, Georg
Abstract: Coarse‐grained samples of Ga‐stabilized tetragonal Li7 La3 Zr2 O12 (LLZO), Li7‐3x Gax La3 Zr2 O12 (x = 0.1—0.6), are obtained by calcination of Li2 CO3 (10 wt% excess), Ga2 O3, La2 O3, and ZrO2 in air (850 °C, 4 h) followed by annealing (1230 °C, 6 h).